PELAYANAN ISTRI TERHADAP KEBUTUHAN SUAMI DAN PENGURUSAN RUMAH TANGGA DALAM PERSPEKTIF ULAMA - Nouvan Moulia (Jurnal Community, 2015)
This study seeks to answer two questions. First, how do Ulamas opinion about the wife care for the daily needs of her husband and the maintenance of the household. Secondly, whether the wife is entitled to compensation for services he did for the daily needs of her husband and taking care of the household. To address these questions the author has conducted research with the literature study approach (library research). The steps travel writers in this research is the collection and analysis of data from primary legal materials, the original material is the basis for the investigation, the legal materials is the Quran, books of tafsir, hadith books and syarahnya, as well as books of fiqh schoolars Hanafiyah, Malikiyah, Shafiiyyah and Hanabilah. Once the data is collected and then processed using content analysis method to be arranged into a research report as a thesis. Cleric Law Schools are divided into two groups in explaining the legal services to the needs of the husband and wife household maintenance. The first group, argued that the wife must serve the needs of her husband and taking care of the household, who think so are scholars Hanafiyah schools and Malikiyah. The second group, argued that the wife is not obliged to perform all of these tasks, which scholarly opinion Shafiiyyah schools and Hanabilah. After doing research, it is known that the wife of work serving the daily needs of her husband and taking care of the household is well accepted custom for generations in the community, but not the obligation to do his wife. The wife is entitled to claim for any service done to prepare for the daily needs of her husband or taking care of the house. Remuneration for his wife do homework set based on the law of al-Ijarah or lease services are allowed in Shari'a.